2015
DOI: 10.13080/z-a.2015.102.052
|View full text |Cite
|
Sign up to set email alerts
|

New non-chemical postharvest technologies reducing berry contamination

Abstract: One of the most important postharvest diseases of strawberry and raspberry is grey mould, caused by Botrytis cinerea Pers.: Fr. New non-chemical food safety technologies reducing berry rots and extending storage time were tested. Photosensitization is an innovative method for inhibition of pathogens in berry and is based on the interaction of light (λ = 400 nm, 20 mW cm -2 ) and photoactive compound (chlorophyllin derivative). The aim of this study was to evaluate the effect of the chlorophyllin-based photosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Despite of the literature scarcity on the effects of electron-beam radiation on raspberries, Guimarães et al (2013) observed an increase on phenolic content of raspberries with gamma radiation at 2 kGy and during storage, while Cabo Verde et al (2013) observed an increase of phenolic content with gamma radiation doses up to 1.5 kGy (T0) with decrease during the storage time. Other preservation technologies tested on raspberries indicated different effects on total phenolic content, namely no effect with chlorophyllin-based photosensitization treatment (Rasiukevičiūtė et al, 2015), or a positive impact (higher level of phenolics) by ozonation process (Piechowiak et al, 2019).…”
Section: Phenolic Content and Antioxidant Activity Of Raspberries Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of the literature scarcity on the effects of electron-beam radiation on raspberries, Guimarães et al (2013) observed an increase on phenolic content of raspberries with gamma radiation at 2 kGy and during storage, while Cabo Verde et al (2013) observed an increase of phenolic content with gamma radiation doses up to 1.5 kGy (T0) with decrease during the storage time. Other preservation technologies tested on raspberries indicated different effects on total phenolic content, namely no effect with chlorophyllin-based photosensitization treatment (Rasiukevičiūtė et al, 2015), or a positive impact (higher level of phenolics) by ozonation process (Piechowiak et al, 2019).…”
Section: Phenolic Content and Antioxidant Activity Of Raspberries Extractsmentioning
confidence: 99%
“…I. Elias, et al Innovative Food Science and Emerging Technologies 66 (2020) 102487 dissimilar effects on antioxidant activity of raspberries, for example, chlorophyllin-based photosensitization treatment had no significant change as measured by DPPH (Rasiukevičiūtė et al, 2015), and ozonation process caused an increase (by DPPH) after treatment and a decrease was detected at 48 h of storage (Piechowiak et al, 2019).…”
Section: Phenolic Content and Antioxidant Activity Of Raspberries Extractsmentioning
confidence: 99%
“…Other combined treatments include the use of nitric oxide, ethylene and low temperatures [103], low density polyethylene with nanoparticles of titanium oxide to actively control the respiration of the fruit [104], Use of specific light intensities after washing the fruits in chlorine solution [105] and the use of nitrogen for strawberry freezing at −20°C after sanitization with 50 ppm chlorine [106].…”
Section: Combined Treatmentsmentioning
confidence: 99%
“…This bioactive compound has been used as a food-grade photosensitizer to reduce microbial growth and to increase the shelf life of freshcut Hami melons (Lin et al 2019), apples (Tao et al 2019), date fruit (Al-Asmari et al 2018), maize kernels (Temba et al 2019) and oysters (Liu et al 2016). Previous studies have shown that photosensitization was successfully applied to decontaminate fungal spores (Al-Asmari et al 2017), Gram-positive and Gram-negative bacteria such as Staphylococcus aureus, Escherichia coli, Salmonella typhimurium (Penha et al 2017) and Vibrio parahaemolyticus (Chen et al 2020) as well as microfungi and yeasts (Rasiukevičiūtė et al 2015). Compared to conventional preservation technologies, photosensitization possesses a stronger antimicrobial effect and is less expensive.…”
Section: Introductionmentioning
confidence: 99%